PI, szeged and edge szeged indices of nanostar dendrimers - Ashrafi, Ali Reza; Mirzargar, Mahsa (Utilitas Mathematica, 2008)
A topological index of a molecular graph G is a numeric quantity related to G which is invariant under symmetry properties of G. A dendrimer is an artificially manufactured or synthesized molecule built up from branched units called monomers. In this paper the PI, Szeged and edge Szeged indices of a class of nanostar dendrimer are computed.